TỔNG HỢP VẬT LIỆU LiNi0,9Mn0,05Co0,05O2 BẰNG PHƯƠNG PHÁP PHẢN ỨNG PHA RẮN (NMC9.5.5-PR) ỨNG DỤNG CHẾ TẠO PIN ION LITI - Lê, Thị Thảo; Nguyễn, Văn Bộ; Phan, Văn Trường; Ngô, Thị Lan; Đoàn, Tiến Phác; Tô, Văn Nguyện (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SYNTHESIS OF LiNi0.9Mn0.05Co0.05O2 BY SOLID-STATE REACTION METHOD (NMC9.5.5-PR) APPLICATION IN MANUFACTURING LITHIUM-ION BATTERIESNickel-manganese-cobalt (NMC) transition metal oxide-based layered structural materials are evaluated a promising material for applications as cathode in lithium-ion batteries. In this study, we have successfully synthesized nickel-rich NMC material LiNi0.9Mn0.05Co0.05O2 by solid-state reaction method (NMC9.5.5-PR). The CR2032-type lithium-ion battery is also successfully fabricated from NMC material to serve the study of electrochemical properties. The NMC9.5.5-PR material exhibits outstanding discharge specific capacity when providing a maximum specific capacity of up to 212.4 mAh/g at a current density of 10 mA/g. However, the cycle efficiency survey results show that the NMC9.5.5-PR material has some disadvantages (only maintaining 81.6% of the discharge specific capacity after 50 continuous charg e-discharge cycles at current density of 10 mA/g). These electrochemical properties indicate that it is necessary to further improve the cyclic efficiency of NMC9.5.5-PR material but preserving its outstanding electrical energy storage capacity. Successfully accomplishing this goal, we believe that NMC-9.5.5-PR or a material based on NMC9.5.5-PR will be one of the suitable materials to fabricate positive electrodes used in lithium-ion batteries.